2018
DOI: 10.1016/j.ijggc.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic evaluation of the 2-amino-2-methyl-1-propanol (AMP) process for CO2 capture from natural gas combined cycle power plant

Abstract: It is widely accepted that emissions of CO 2 , which is a major greenhouse gas, are the primary cause of climate change. This has led to the development of carbon capture and storage (CCS) technologies in which CO 2 is captured from large-scale point sources such as power plants. However, retrofits of carbon capture plants result in high efficiency penalties, which have been reported to fall in the range of 7-12% points in the case of post-combustion capture from natural gas-fired power plants. Therefore, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Results showed that the MEA process had lower energy requirements as compared to Cesar 1. Energy consumption accounts for about 25% of total cost thus, the AMP solvent, which has more favourable operating parameters as compared to the MEA solvent as shown in studies [23,28,29] will further minimize energy requirements which will reduce cost. It is therefore important to develop these configurations and utilize the energy savings provided.…”
Section: Mea Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the MEA process had lower energy requirements as compared to Cesar 1. Energy consumption accounts for about 25% of total cost thus, the AMP solvent, which has more favourable operating parameters as compared to the MEA solvent as shown in studies [23,28,29] will further minimize energy requirements which will reduce cost. It is therefore important to develop these configurations and utilize the energy savings provided.…”
Section: Mea Nomentioning
confidence: 99%
“…The AMP-based process model was developed using the operating parameters in Aspen Plus ® software Version (V) 8.4 (Aspen Technology, Inc., Bedford, MA, USA, released in 2013), and consists of an absorber and a stripper column, with a cross heat exchanger and a pump, all connected in a closed loop cycle as described in studies [26,31]. The validation of the capture plant model with experimental data is presented in the literature [26,28].…”
Section: Model Description Of the Capture Plantmentioning
confidence: 99%
“…The model includes two columns: the ABSORBER and the STRIPPER (RadFrac); a water wash section, WATERWAS (SEP) where any residual solvent is removed from the clean flue gas; a make-up section, MAKE-UP (MIXER) which allows the addition of both H 2 O and MEA to ensure the lean amine stream inlet to the absorber is of the correct composition. The five-stage intercooled compression train [9,15,24] used to process the captured CO 2 for storage is comprised of a series of four compressors, COM1-4 (COMPR), knock out drums, KO1-4 (FLASH) to remove residual water and intercoolers, IN-COOL1-4 (HEATER) to reduce the temperature of the CO 2 ; this puts the CO 2 into the supercritical fluid state where the 5th stage, a pump, CO2PUMP (PUMP) increases the pressure of the CO 2 to 140 bar. The cross-heat exchanger, HEATX (HEATX) is used to heat the rich amine stream using the waste heat in the lean stream and the BLOWER (COMPR) is used to increase the flue gases pressure to overcome the pressure drop in the column.…”
Section: Of 16mentioning
confidence: 99%
“…A description of the chemical absorption that takes place in a PCC system can be achieved by modelling, using either an equilibrium or rate-based mass-transfer, with a number of studies being validated against pilot plant data [9,12,[22][23][24]. Rate-based simulations can provide a greater accuracy and allow a more informed evaluation of the process [12,14,17,[23][24][25][26] but equilibrium approaches can still be employed for process assessment [11,19,27,28]. The relative simplicity of an equilibrium approach and the ability to improve the accuracy of such a model with stage efficiencies [16,19,[29][30][31] is the justification for employing such a strategy here.…”
Section: Introductionmentioning
confidence: 99%
“…Each of them entails different capture technologies (absorption, adsorption, membrane separation, etc. ), and absorption is the most frequently used technology for carbon dioxide capture from flue gases [7,8]. Even if several solvents can be used, monoethanolamine (MEA) is the most widely used due to its high reactivity, low cost, good absorption capacity, and high affinity to carbon dioxide [9].…”
Section: Introductionmentioning
confidence: 99%